THE SPACE IN BETWEEN: NARRATIVES OF SILENCE AND GENETIC TERMINATIONS - Thachuk, Angela (Bioethics, 2007)
In North America, prenatal testing and genetic terminations are becoming clinically normalized. Yet despite this implied social acceptance, open discussions surrounding genetic terminations remain taboo and silenced. Women are socially isolated, their experiences kept secret, and their grief disenfranchised. The lack of social consensus regarding genetic terminations, the valorization of scientific knowledge, and the bioethical framing of the issue as a matter of personal choice and autonomy collectively serve to reify this silence. In many respects genetic screening offers a form of technological surveillance procuring security from the unwanted kind of child. Yet the manner in which ‘the unwanted kind of child’ is understood varies from context to context. While we carry with us the consequences of decisions made elsewhere, the institutionalized discourses upon which these decisions are made are not always so readily transportable. One must somehow reconcile ‘the unwanted kind of child’ of the biomedical model with ‘the unwanted kind of child’ who was to be a member of one's family. In this paper, my intention is not to engage in the broader debate surrounding prenatal testing and genetic terminations. Rather, I employ my clinical encounters with these practices to illustrate the absence of an ethical language that might do justice to the experiences such practices construct. The limitations of a bioethical discourse that remains abstracted from lived experience are discussed.